Juicios paralelos y condenas sociales como equivalentes funcionales de la pena - Bide, Jerónimo (Pontificia Universidad Católica del Perú, 2024)
In this article will be defended the thesis that parallel trials and social condemnations can often serve as functional equivalents to forensic punishment –most of the times, only partially– and, insofar as they justify a reduction in the formal sentence, should be considered during the judicial sentencing process.To support this argument, which is considered correct if the proportionality of penalties is to be consistently respected, the author will begin with the theory of norms, focusing particularly on the sanction norm; then introduce the theory of functional equivalents to punishment, considering both its factual and expressive dimensions and finally, analyze how both retributive and preventive aspects, along with considerations of desert and necessity, influence the determination of punishment.

En este artículo se defenderá la tesis de que los juicios paralelos y condenas sociales pueden fungir muchas veces como equivalentes funcionales de la pena forense –generalmente, solo de modo parcial–, y, en la medida en que fundamenten una atenuación del castigo, deberán ser descontadas de este al momento de su individualización judicial.Para llegar a esta solución, que se considera correcta si se quiere respetar consecuentemente la proporcionalidad de las penas, el autor partirá desde la teoría de las normas prestando especial atención a la norma de sanción, planteará la teoría de los equivalentes funcionales a la pena a partir de su doble dimensión fáctica y expresiva, y analizará cómo juegan en la medición de la pena tanto los aspectos retributivos y preventivos como el merecimiento y la necesidad.
Parallel trials and social condemnations as functional equivalents to punishment: arguments in favor of a sentence reduction due to certain social reactions
Keywords: Parallel trials and social condemnations; Functional equivalents to punishment; Prevention and retribution; Sanction norm; Necessity of punishment; Juicios paralelos y condenas sociales; Equivalentes funcionales de la pena; Prevención y retribución; Norma de sanción; Necesidad de pena; https://purl.org/pe-repo/ocde/ford#5.05.01